1987
DOI: 10.1111/j.1432-1033.1987.tb11204.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic gels from macrophages

Abstract: A method has been devised to study the influence of Ca2+ on the in vitro formation of actin gel networks. Under appropriate conditions low-Ca' + cytosolic extracts ( < 1 nM) from macrophages rapidly formed a macromolecular complex composed of actin, filamin, a-actinin and two new proteins of 70 kDa and 55 kDa. [Pacaud, M. (1986) Eur. J . Biochem. 156, Increasing concentrations of free Ca2+ to 1 -2 pM resulted in complete inhibition of the association of 70-kDa protein, a protein which associates actin filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…The discovery of a potential calcium-binding site in Lplastin is consistent with the identity of this isoform with a protein previously identified in human macrophages by Pacaud (13) and Pacaud and Molla (14) that exhibited the same molecular weight (approximately 70,000) and isoelectric point (pl 5.3) as L-plastin in two-dimensional gels. We have previously shown that L-plastin is one of the most…”
supporting
confidence: 62%
See 1 more Smart Citation
“…The discovery of a potential calcium-binding site in Lplastin is consistent with the identity of this isoform with a protein previously identified in human macrophages by Pacaud (13) and Pacaud and Molla (14) that exhibited the same molecular weight (approximately 70,000) and isoelectric point (pl 5.3) as L-plastin in two-dimensional gels. We have previously shown that L-plastin is one of the most…”
supporting
confidence: 62%
“…The macrophage protein was shown to bind to polymerized actin in a calcium-dependent manner (13,14). Also, Matsushima and co-workers (12) have purified L-plastin from human macrophages (identified as L-plastin by sequence [8]) and have demonstrated that it is phosphorylated at serine residues.…”
mentioning
confidence: 99%
“…In addition to actin and filamin (Hartwig & Stossel, 1975, 1981, other major components of these gels include two actin-bundling proteins, a-actinin and a new 70-kDa1 protein, and two unidentified molecules of 55 kDa and 17 kDa (Pacaud, 1986). We were subsequently able to demonstrate that a rise in the free calcium concentration of cytosolic extracts, within the 0006-2960/93/0432-3448504.00/0 physiological range, could trigger sequential changes in the protein composition of actin gels (Pacaud & Molla, 1987). Further studies on isolated cytoplasmic gels and purified 70-kDA protein led us to suggest that Ca2+ control of the interactions between this protein and F-actin may exert a dominant influence in regulating the state of microfilament organization (Pacaud & Harricane, 1987).…”
mentioning
confidence: 82%
“…Further studies on isolated cytoplasmic gels and purified 70-kDA protein led us to suggest that Ca2+ control of the interactions between this protein and F-actin may exert a dominant influence in regulating the state of microfilament organization (Pacaud & Harricane, 1987). Despite the established view that non-muscle a-actinin is a calciummodulated protein (for a review see Pollard and Cooper (1986), calcium had no effect on the association of a-actinin with F-actin in cytoplasmic gels (Pacaud & Molla, 1987).…”
mentioning
confidence: 99%
“…Examples of known Ca 2 § dent interactions of CaM with actin-binding proteins include several proteins that cross-link actin filaments like erythrocyte adducin (Mische et al 1987), those that link actin filaments to other proteins (Anderson and Morrow 1987;Okabe and Sobue 1987), and those regulating smooth-muscle contraction including fodrin (Wang et al 1987), caldesmon (Sobue et al 1988), and myosin light-chain kinase (Yagi et al 1978). In addition, CaM is known to increase the rate of polymerization of F-actin in human platelets (Piazza and Wallace 1985) and to affect actin gelation (Kotani et al 1985;Pacaud and Molla 1987). In Ernodesmis CaM may bind to and activate a yet-unidentified protein, which in turn regulates actin-based motility in these cells.…”
Section: Discussionmentioning
confidence: 97%